Development of biomechanical lumbar support for ergonomics bus seat - Wan Hassan, Wan Chik Zaharah; Mohd Tamrin, Shamsul Bahri; Abdul Hamid, Hamiraj Fahry; Raja Ahmad, Raja Adzrin; Mohd Yusuff, Rosnah; Hamzah, Rosnan; Abdul Aziz, Nasaruddin; Jalaludin, Juliana; Nordin , Rusli; Naing, Lin; Awang, Mazlan (2005)
In many commercial vehicles, the driver is definitely exposed to ergonomics hazards that may contribute to spinal stress and its supportive structures that can cause low back pain. In order to decrease the effects of workloads on the body that can cause back problem, therefore there is a need to modify the bus seat itself. The solution is to design a new seat to support the back in a posture, which minimizes spinal stress, and to isolate the seat from the effects of muscle fatigues. One of criteria in developing an ergonomics bus seat in reducing low back pain is the development of a new seat that includes biomechanical lumbar support. A biomechanical lumbar support was designed using three main major components namely ergonomics data collected from Malaysian bus drivers, mechanical components and electrical components in fabricating a biomechanical lumbar support. This new development of ergonomic bus seat was designed based on Malaysian anthropometry with 7 mechanical components with movement controlled and synchronized by back massaging electronic motor system. The electronic motor system will allow the driver to set the lumbar support in motion on a periodical basis. The timer has a range from 15 minutes to 30 minutes with a duration that ranges from 30 seconds to 90 seconds per lumbar support back massaging system. The system also have a control that allows the driver to manually use of the system provided when the driver at rest or driving. From this research study, a new design of ergonomics bus seat consists of biomechanical lumbar support that based on Malaysian anthropometric male bus drivers, together with the mechanical design and electrical and electronic design, finally will develop and realization as a new bus seat that can reduce low back pain among commercial vehicle drivers in Malaysia.